2018
DOI: 10.3892/or.2018.6398
|View full text |Cite
|
Sign up to set email alerts
|

Glycine and succinic acid are effective indicators of the suppression of epithelial-mesenchymal transition by fucoxanthinol in colorectal cancer stem-like cells

Abstract: Fucoxanthinol (FxOH) is a strong anticancer metabolite of fucoxanthin that accumulates in abundance in edible brown algae and promises human health benefits. FxOH has been shown to suppress tumorigenicity and sphere formation in human colorectal cancer stem cell (CCSC)-like spheroids (colonospheres, Csps). In the present study, we aimed to clarify the inhibitory activity of FxOH on epithelial-mesenchymal transition (EMT), which is essential for cancer recurrence and distant metastasis, and to identify intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…The disparity of gene expression responses between the 24h and 48h time points for fucoxanthin may indicate that this compound exhibits more complex drug-induced gene expression effects over time than does LY-294002. This hypothesis requires further investigation but is consistent with the observed metabolic lability of fucoxanthin in whole animal studies and the production of a new antiproliferative active metabolite, fucoxanthinol [77]. In parallel experiments not reported here, we have confirmed that fucoxanthinol inhibits U87MG cell proliferation, but do not yet know whether fucoxanthin is extensively metabolized to fucoxanthinol by glioblastoma cells themselves.…”
Section: Plos Onesupporting
confidence: 81%
“…The disparity of gene expression responses between the 24h and 48h time points for fucoxanthin may indicate that this compound exhibits more complex drug-induced gene expression effects over time than does LY-294002. This hypothesis requires further investigation but is consistent with the observed metabolic lability of fucoxanthin in whole animal studies and the production of a new antiproliferative active metabolite, fucoxanthinol [77]. In parallel experiments not reported here, we have confirmed that fucoxanthinol inhibits U87MG cell proliferation, but do not yet know whether fucoxanthin is extensively metabolized to fucoxanthinol by glioblastoma cells themselves.…”
Section: Plos Onesupporting
confidence: 81%
“…Our previous studies demonstrated that glycine and succinic acid under normoxia or glycine under hypoxia were metabolite indicators correlated with suppression of sphere formation and epithelial mesenchymal transition due to FxOH treatment in Csps. (25,26) In the present study, the tumor glycine content in the xenograft mice was significantly decreased by Fx administration to 0.5-fold (Fig. 5 and Table 2).…”
Section: Discussionsupporting
confidence: 61%
“…(2224) We have recently reported that intracellular glycine and succinic acid indices correlated with suppression of sphere formation due to FxOH treatment in Csps. (25,26) Moreover, we have recently demonstrated that FxOH induces apoptosis in Csps and inhibits their tumorigenicity in a xenograft mouse model, (27) while previous studies have not explored differences of biological metabolites in tumor-bearing mice with FxOH or Fx administration.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in a dose-dependent manner, FxOH inhibited sphere formation. These effects were associated with suppressed migration and invasion [104].…”
Section: Xanthophyllsmentioning
confidence: 97%